2006
DOI: 10.1364/oe.14.001253
|View full text |Cite
|
Sign up to set email alerts
|

Shape resonance omni-directional terahertz filters with near-unity transmittance

Abstract: Terahertz transmission filters have been manufactured by perforating metal films with various geometric shapes using femtosecond laser machining. Two dimensional arrays of square, circular, rectangular, cshaped, and epsilon-shaped holes all support over 99% transmission at specific frequencies determined by geometric shape, symmetry, polarization, and lattice constant. Our results show that plasmonic structures with different geometric shaped holes are extremely versatile, dependable, easy to control and easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 30 publications
(28 reference statements)
1
52
0
Order By: Relevance
“…In the terahertz regime, SPs have recently attracted much attention and become an attractive new area [10][11][12][13][14][15][16][17][18][19]. Due to a drastic increase in the value of dielectric function ε m = ε rm + iε im , most metals become highly conductive at terahertz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In the terahertz regime, SPs have recently attracted much attention and become an attractive new area [10][11][12][13][14][15][16][17][18][19]. Due to a drastic increase in the value of dielectric function ε m = ε rm + iε im , most metals become highly conductive at terahertz frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Klien and co-workers [7][8][9][10][11][12][13][14][15][16][17] have experimentally found that the hole shape also has a strong effect on the transmission characteristics of MHAs; this effect is known as localized resonance, and it has been investigated extensively. Ruan et al 9 have calculated the transmission spectra of periodically arranged and randomly distributed rectangular holes and found a transmission peak whose frequency is almost independent of the period.…”
mentioning
confidence: 99%
“…In this sense, a well-designed aperture can be the most efficient way of focusing electromagnetic energy beyond diffraction limit [2], provided that a resonant condition for large near-field enhancement is met. This type of near-field focusing is implicit in many experiments, including far-field transparency [3,4] at the fundamental resonance [5][6][7]. Near-field enhancement [8] and focusing would be particularly desirable in the terahertz range where most tabletop laboratory sources are too weak to induce, for example, nonlinear effects or to detect single molecules [9][10][11].…”
mentioning
confidence: 99%